Asymmetric impact of oil price and exchange rate on disaggregation price inflation. (October 2021) - Husaini, Dzul Hadzwan; Lean, Hooi Hooi
Abstract: Maintaining price stability is crucial for meaningful economic growth. However, while policymakers tend to remove some energy incentives when the oil price decreases to moderate fiscal pressure, a decrease in oil price interacts with the exchange rate depreciation in the oil exporting country. This is the first study that examines the asymmetric impact of both oil price and exchange rate on the disaggregate price inflation in Indonesia, Malaysia, and Thailand. Given that each country has its own economic structure, the impact of oil price and exchange rate fluctuation on the price level may differ across the countries. We find that an increase in oil price has a greater impact on the producer price index (PPI) than the consumer price index (CPI) in all countries. However, a decrease in the oil price is only significant in reducing both CPI and PPI in Thailand. Moreover, an increase in the exchange rate (currency depreciation) is significant in causing an increase in both the CPI and PPI in all countries. However, a decrease in the exchange rate (currency appreciation) failed to reduce both the CPI and PPI in all countries. We recommend that policymakers continue their energy incentive programs, however, the distribution of the energy incentive should be improved to ensure that the benefit reaches the targeted group. Highlights: We explore the asymmetric impact of oil price and exchange rate respectively on inflation. An increase in oil price gives greater impact on PPI than CPI. An increase in exchange rate is significant to cause an increase in both CPI and PPI. We recommend the policymakers to continue their energy incentive programs. Strengthening monetary policy and increase their efficiency are also recommended.